Pengaruh Partisipasi Masyarakat Desa Lumban Dolok terhadap Kegiatan Nuzulul Qur’an - Aisyah Nur Dalimunthe; Syamsiah Depalina Siregar (Jurnal Pendidikan dan Humaniora Rumbio, 2026)
This research aims to analyze the influence of community participation in Nuzulul Qur'an competitions on the learning motivation of Islamic Religious Education in Lumban Dolok Village. Nuzulul Qur'an commemoration is an important momentum for Muslims to remember the revelation of the Qur'an and strengthen religious values through various competitions such as tahfidz, Al-Barzanji, funeral prayer, and adhan. This research uses a quantitative approach with an explanatory method involving 45 community members who participate in the competitions. Data were collected through questionnaires using a Likert scale, observation, and documentation, then analyzed using descriptive statistics and simple regression analysis. The results showed that community participation in Nuzulul Qur'an competitions had a significant positive effect on Islamic Religious Education learning motivation with a regression coefficient of 0.687 and significance value of 0.000 (p<0.05). The R Square value of 0.472 indicates that community participation explains 47.2% of the variation in learning motivation. This research provides theoretical contributions regarding the relationship between community-based religious activities and religious learning motivation, as well as practical implications for improving the quality of religious activities in the future.